"Stop, You're Killing us!" An Alternative Take on Populism and Public Health; Comment on "The Rise of Post-truth Populism in Pluralist Liberal Democracies: Challenges for Health Policy" - Ted Schrecker (Kerman University of Medical Sciences, 2017)
Ewen Speed and Russell Mannion correctly identify several contours of the challenges for health policy in what it is useful to think of as a post-democratic era. I argue that the problem for public health is not populism per se, but rather the distinctive populism of the right coupled with the failure of the left to develop compelling counternarratives. Further, defences of 'science' must be tempered by recognition of the unavoidably political dimensions of the (mis)use of scientific findings in public policy.